From Monasteries to Multinationals (and Back): A Historical Review of the Beer Economy - Eline Poelmans; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2011)
This article reviews beer production, consumption and the industrial organization of breweries throughout history. Monasteries were the centers of the beer economy in the early Middle Ages. Innovation and increased demand later induced the growth of commercial breweries. Globalization and scientific discoveries transfirmed the beer industry and increased competition from the 16th through the 19th century. The 20th century was characterized by dramatic (domestic and international) consolidation, major shifts in consumption patterns, and the re-emergence of small breweries.
Keywords: N30; N40; L23; L66; 330; economic history; history of beer; monasteries; innovation and taxation in brewing; modern brewing; consolidation and globalization